A Novel Quaternary Ammonium N-Propylamiodarone Bromide Provides Long-Lasting Analgesia Against Corneal Pain - Kotoda Y; Hishiyama S; Shim J; Kobayashi H; Takamino A; Abe M; Kashiwagi K; Matsukawa T; Kotoda M (Drug Design, Development and Therapy)
Yumi Kotoda,1 Sohei Hishiyama,2 Jaehoon Shim,3,4 Hiroki Kobayashi,2 Ayasa Takamino,2 Masako Abe,2 Kenji Kashiwagi,1 Takashi Matsukawa,2 Masakazu Kotoda2 1Department of Ophthalmology, Faculty of Medicine, University of Yamanashi, Chuo, Yamanashi, Japan; 2Department of Anesthesiology, Faculty of Medicine, University of Yamanashi, Chuo, Yamanashi, Japan; 3F.M. Kirby Neurobiology Center and Department of Neurology, Boston Children’s Hospital, Boston, MA, USA; 4Department of Neurobiology, Harvard Medical School, Boston, MA, USACorrespondence: Masakazu Kotoda, Department of Anesthesiology, Faculty of Medicine, University of Yamanashi, 1110 Shimokato, Chuo, Yamanashi, Japan, Tel +81-55-273-9690, Email mkotoda@yamanashi.ac.jpPurpose: Corneal pain is one of the most common eye symptoms caused by various types of epithelial injuries, including traumatic abrasion, chemical injury, ulcers, ultraviolet exposure, and infection. However, current therapeutic options for corneal pain are limited. In this study, we synthesized a novel quaternary ammonium compound, N-propylamiodarone bromide (NPA), and employed a rodent model of corneal injury to investigate whether NPA offers prolonged corneal analgesia through transient receptor potential vanilloid 1 (TRPV1) channel-mediated selective cellular entry, without hindering corneal epithelial recovery.Methods: In the corneal injury model, 24 adult Wistar rats received a topical application of normal saline, oxybuprocaine, or NPA (n = 8 each), and corneal pain sensitivity was assessed using the von Frey technique. Another set of 32 rats with intact corneas received oxybuprocaine, capsaicin (a TRPV1 agonist), or NPA with or without capsaicin (n = 8 each), followed by a mechanical sensitivity evaluation. Potential adverse effects on normal epithelial recovery were evaluated using fluorescence and hematoxylin–eosin staining in an additional 8 rats with corneal injury.Results: In the corneal injury model, NPA produced significantly longer-lasting analgesia than oxybuprocaine (duration of the maximum effect: 215 ± 11 vs 25 ± 2 min, P < 0.001). None of the animals presented any signs of eye irritability. In contrast to injured eyes, NPA alone did not significantly increase mechanical sensitivity in naïve eyes. However, the co-administration of NPA and capsaicin produced significantly longer-lasting corneal anesthesia than oxybuprocaine (duration of the maximum effect: 165 ± 15 vs 31 ± 2 min, P < 0.001). NPA did not hamper wound healing.Conclusion: The novel quaternary ammonium NPA produced long-lasting analgesia against corneal injury without hampering corneal recovery, suggesting that it is a potential candidate for analgesic medicine targeting corneal pain.Keywords: analgesics, capsaicin, corneal injury, pain, TRPV1 channel